The Influence of Corporate Governance Mechanisms on the Performance of Commercial Banks in Indonesia - Desi Natalia Lumbantoruan; Cantika Nasywa Suryatna; Susy Muchtar (Universitas KH. Abdul Chalim Mojokerto, 2025)
The banking sector has an important role in supporting sustainable economic growth in Indonesia. However, global economic uncertainty and changes in monetary policy require improved corporate governance mechanisms to maintain financial stability and performance. This study aims to analyze the influence of corporate governance mechanisms, which include Board Size, Board Independence, Capital Adequacy Ratio (CAR), and Firm Sizeon the performance of commercial banks in Indonesia, which is proxied by Earnings Per Share (EPS). This study uses a panel data regression method with a sample of commercial banks listed on the Indonesia Stock Exchange (IDX) from 2019-2023. Secondary data was obtained from financial reports and official publications. The study results showed no influence of Board Size, Board Independence, Capital Adequacy Ratio, and Firm Size towards increasing EPS. This study is expected to contribute to understanding the factors that influence bank performance in Indonesia and become a reference for regulators and bank management to improve sustainable corporate governance.